REFERENDUM BREXIT DAN KEMBALI MENGEMUKANYA KEDAULATAN NEGARA SERTA DAMPAKNYA BAGI DUNIA DAN INDONESIA - Hartanto Hartanto (Populis : Jurnal Sosial dan Humaniora, 2016)
This article attempts to explain the Brexit phenomenon from the standpoint of international relations. The Brexit referendum is a milestone of the UK that decide to leave from the European Union, which has never been a member country that came out before, of course, provide a very spacious negative and positive impacts for the England, the United Kingdom and of course the rest of the World. England’s choice to withdraw from membership in the European Union of course should be respected, but if the terms of the International Relations science it can be interpreted as a discovery of meaning back from the perspective of realism that has long been considered obsolete and is currently the England prefer to give priority to the country's sovereignty. Keywords: Brexit, Referendum, Sovereignty